(untitled) (Raparin Journal of Humanities (RJH), 2025)
The aim of this study is to investigate the relationship between positive thinking and Emotional Stability among educational counselors in high schools in Sulaymaniyah city. This study also aims to identify the level of positive thinking and emotional stability according to variables such as (gender, years of service (among the study sample. the researcher used the descriptive method in the study. The population of this study comprises all educational counselors employed in high schools within Sulaymaniyah city, totaling 178 individuals of both male and female genders. The study employed a comprehensive survey method, selecting the entire research population as the sample. The instruments employed in this study comprised of: "Positive Thinking Level" scale which the researcher prepared and an "Emotional Stability Level" scale adapted from prior research. The validity and reliability of the measures having been established, they were thereafter applied to the research sample. The most important statistical tools used were (T-Test, ANOVA, Pearson correlation, arithmetic mean, standard deviation). The results of this study showed that, a high level of positive thinking was observed among educational counselors, and educational counselors also demonstrated a high level of emotional stability, however a strong positive correlation was found between positive thinking and emotional stability. Based on the findings of this study, several recommendations and suggestions are presented.